Finite Element Evaluation of Full 3D Effective Properties Of d₃₁ Piezoelectric Macro-Fibre Composites - Trindade, Marcelo A. (2024)
Piezoelectric Macro-Fibre Composites (MFC) transducers have become very popular since they combine the conformability of epoxy-matrix composites and the electromechanical energy density of piezoceramic materials. Since they are heterogeneous and made of several different materials (piezoceramic fibres, epoxy matrix, electrode and protective layers), a methodology is required to relate their effective properties with the individual properties of its components. This work presents the evaluation of all necessary effective properties for a full 3D finite element analysis. For the evaluation of the remaining effective piezoelectric coefficients, new local problems were added to those presented in the l iterature. The results are compared to those available in the literature and provided by the manufacturer. A discussion on the full 3D effective properties and their application for full 3D finite element analysis of smart structures with bonded MFCs is also presented.